Nutritional and Physical Evaluation of Selected Pearl Millet Cultivars - Bhati, Dashrath; Goyal, Madhu (Asian Journal of Chemistry, 2012)
A comparative study was carried out on nutritional and physical qualities of nine cultivars (three in each group of hybrid, composite and land races) of pearl millet (Pennisetum glaucum) grown in I-C zone of Rajasthan. The estimated mean values for moisture, protein, fat, ash, fiber, carbohydrates and energy on g per cent basis were found to be ranging as 4.79 to 7.81, 8.59 to 10.71, 5.17 to 10.28, 1.24 to 2.06, 1.86 to 3.66, 69.20 to 74.76 and 396 to 421 Kcal respectively. Fat content was found to be maximum in RHB 121 (10.28 g) and minimum in Jaisalmeri Desi (5.17 g). Protein content was found to be higher in land races followed by composite and hybrid. The total soluble sugar, reducing sugars and non-reducing sugars were ranging from 1.77 to 2.08, 1.30 to 1.80 and 0.24 to 0.79 %. The per cent values for calcium, phosphorus and iron ranged between 396 to 421 Kcal, 29.47 to 60.15, 256.79 to 398.84 and 5.24 to 7.94 mg per cent respectively. The values for physical characteristics like seed weight, seed volume, seed density, hydration capacity, swelling capacity, seed germination per cent were ranging between 5.01 to 8.64 g/1000 seed, 0.017 to 0.043 m/seed, 0.780 to 0.860 g/mL, 0.0027 to 0.0037 g/seed, 0.0018 to 0.0033 mL/seed and 86.86 to 95.94 per cent respectively with significant variation between the variation at five per cent level of significance. Seed weight was noted high in all the hybrid cultivars as compare to land races and composite verities. Amount of antinutritional factors like polyphenols and phytic acids was noted to be ranging from 261.11 to 653.47 mg per cent and 48.65 to 84.75 mg per cent respectively. The varieties in nutritional and physical qualities of pearl millet cultivars varied widely and found to be independent of the type of sub groups of their varieties i.e. hybrid, composite and land races.